Picturing Hagiography: The relationship between text and image in Ms BnF NAL 868 - María López-Monís Yuste (Revista de Poética Medieval)
The group of illuminations in Ms BnF Nouvelles Acquisitions Latines 868, made in Castile c. 1280, conforms one of the few preserved medieval examples of pictorial cycles representing the life of St Elizabeth of Hungary, and the only 13th-century one created outside Marburg, where Elizabeth’s remains were buried. This fact, combined with the lack of information regarding its origin and fortune, make this manuscript an object of great interest, especially given its clear ties with the scriptorium of king Alfonso X. This article will focus on the construction of the Old Castilian rubrics, created expressly for this codex, and on the interaction between Latin text, Old Castilian rubrics, and images. By doing so, this article aims to showcase the role of Juan Gil de Zamora as intellectual creator of the manuscript’s textual and figurative cycles.